The development of dehydrated mashed potatoes on a labaratory scale - Mori, Elizabeth M.
A dehydrated mashed potato product was developed utilizing the Fina Variety as raw material. Objective tests on specific gravity, total solids, starch, and sugar content indicated that this variety is more suitable than the Red Pontiac variety for processing purposes. Analysis of different mixtures of seed powder to freshly-cooked potatoes showed that a 50% by weight proportion yielded the highest rehydration ratio. The optimum dehydration temperature was set at 150 to 16°F for a total drying time if 5 1/2 hours. In order to minimize losses due to the agglomeration of the granules, screening was deemed necessary while the potatoes had a moisture content of approximately 56.5%. From the results of the sensory evaluation, the reconstituted product was standardized 4 ml. of water per gram of potato powder.